KELIMPAHAN POPULASI DAN PERBEDAAN MORFOMETRI Telescopium telescopium PADA HABITAT MANGROVE DI SUNGAI BONGKOK KAMPUNG BAGAN TANJUNG PIAYU DAN DI SEKITAR TPA PUNGGUR KOTA BATAM - Yarsi Efendi; Ramses Ramses; Adil Waraney (Universitas Riau Kepulauan, 2014)
The Research have done started from February to June 2013, have purpose to compare the population abudance and difference of morphometric Telescopium telescopium in two different observation places. The sampling point determined by method of random sampling. The sample has taken by plot measurement 10x10 m and the sub plot measurement 1x1 m placed in 5 pieces plot measurement 10x10 m.The research result got 62 individual Telescopium telescopium in research location with the density value 0.155 (ind/m²) at 1st location and 297 individual Telescopium telescopium with the density value 0.7425 (ind/m²) at 2nd location. The average measurement result (length and dimeter) morphometric of Telescopium telescopium found at mangrove habitat in Sungai Bongkok was length 8.94 cm and diameter 4.73 cm. The morphometric average measurement result (length and diameter) Telescopium telescopium found at mangrove habitat around the garbage disposal Punggur was length 4.66 cm and diameter 2.54 cm. Keywords: Population Abundance; Morphometric; Telescopium telescopium.